Proceedings of the XII International Symposium on Biological Control of Weeds, La Grande Motte, France, 22-27 April, 2007 - Julien, M. H.; Bon, M. C.; Bon, M. C.; Evans, H. C.; Evans, H. C.; Hatcher, P. E.; Hatcher, P. E.; Hinz, H. L.; Hinz, H. L.; Julien, M. H.; Rector, B. G.; Rector, B. G.; et al. (Wallingford :CAB International, 2008)
These proceedings contain the full-length papers and abstracts of papers presented at the symposium. Subjects covered include: ecology and modelling in biological control of weeds; benefits, risks and cost analysis of biological weed control; target and biological control agent selection; pre-release specificity and efficacy testing; regulations and public awareness; evolutionary processes; opportunities and constraints for the biological control of weeds in Europe; release activities and post-release evaluations; and management specifics, integration, restoration and implementation.
Keywords: DD500 - Laws and Regulations; EE110 - Agricultural Economics; FF500 - Weeds and Noxious Plants; HH100 - Biological Control; ZZ100 - Mathematics and Statistics; ZZ331 - Plant Ecology; ZZ380 - Taxonomy and Evolution; Europe